Communities of Practice: Art, Play, and Aesthetics in Early Childhood (Landscapes: the Arts, Aesthetics, and Education,, 2018)
Reflecting contemporary theory and research in early art education, this volume offers a comprehensive introduction to new ways of thinking about the place of art, play, and aesthetics in the lives and education of young children. Enlivened by narratives and illustrations, 16 authors offer perspectives on the lived experience of being a child and discovering the excitement of making meaning and form in the process of art, play, and aesthetic inquiry. "Advocates of the arts and play in early childhood have long challenged the narrative of the universal child and contested binaries such as adult/child, play/learning, and mind/body. Communities of Practice: Art, Play, and Aesthetics in Early Childhood is pivotal because it elegantly portrays subtle yet critical shifts in thinking. This collection of perspectives from around the globe poses new questions and offers up fresh perspectives. Each chapter explicates theoretical inspirations and includes stories and images to bring ideas to life. This book is an essential read because it not only challenges conventional thinking, but also sheds light on exciting new pathways." Jolyn Blank, University of South Florida, USA.